Europäische Bankenregulierung und private Haftung Die Durchsetzung von System- und Individualschutz mit Mitteln des Privatrechts. - Badenhoop, Nikolai (Schriften zum Unternehmens- und Kapitalmarktrecht., 2020)
EU banking regulation serves not only to safeguard financial markets as a whole, but also to protect each individual bank customer, especially depositors, investors, and consumers. Private law mechanisms such as claims for damages can complement public supervision effectively. For this reason, Nikolai Badenhoop makes the case for stronger private law enforcement.